(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The purpose of this article is to show that some Christian principles are in fact supported by the most important law of Brazil: the Federal Constitution. In truth, Christianism played a relevant role, influencing the elaboration of the basic constitutional norms.